PENGARUH PEMBIAYAAN MUDHARABAH DAN PEMBIAYAAN MUSYARAKAH TERHADAP TINGKAT PROFITABILITAS PADA PT. BANK SYARIAH INDONESIA (BSI) PERIODE TAHUN 2021-2023 - Wulandari; Sumar'in (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2025)
Profitability is a ratio that looks at a company's ability to generate profits. Sharia banking is an institution that provides sharia banking services based on sharia principles. This research aims to determine the effect of mudharabah and nausyarakah financing on the level of profitability at PT. Bank Syariah Indonesia, Tbk period talfun 2021-2023. This research is a quantitative research with the data source used is secondary data obtained through the official website of Bank Syariah Indonesia.. The number of samples in this study was 36 samples. The analysis techniques used include statistical analysis, multiple linear regression analysis, hypothesis testing, namely the t test, using SPSS 24 analysis tools. The results of the research show that the mudharabah variable, the t-calculated results of the mudharabah variable, do not have a significant effect on ROE. The musyarakah variable from the t-calculated musyarakah variable has a significant positive effect on ROE. And by testing all the independent variables simultaneously, it was found that the influence of mudharabah and musyarakah financing on ROE is that the R Square value is 0.311, which means that the contribution of the two independent variables of mudharabah and musyarakah to ROE is 31.1%, and 68.9% of the other variables